Suppression of Lanthanide Clustering in Glass by Network Topological Constraints. Issue 10 (18th August 2015) - Guo, Qiangbing; Liu, Xiaofeng; Zhou, Shifeng
Abstract : Here, we demonstrate the relationship between glass network topological structure and the chemical state of embedded lanthanide ions. It is revealed that a more dispersed state of lanthanide ions is shown in more constrained 3D rigid network, which delivers valuable information toward homogeneous doping in glasses from the perspective of glass topological structure. The results are believed to be of great significances in the development of advanced optoelectronic devices like high‐power laser, efficient fiber amplifier, smaller integrated photonic circuit, etc.